Understanding parents' school travel choices: A qualitative study using the Theoretical Domains Framework. (March 2017) - Ahern, Sara M.; Arnott, Bronia; Chatterton, Tim; de Nazelle, Audrey; Kellar, Ian; McEachan, Rosemary R.C.
Abstract: Traffic related air pollution is detrimental to health and creates a substantial attributable mortality burden. It is suggested that a shift from motorised transport to active forms of travel will therefore have significant health benefits. Currently 46% of school journeys for primary aged children are made by car and this figure has risen steadily. Understanding barriers to active school travel (AST) is an important first step in developing behavioural interventions to increase active travel. The purpose of this study was to explore parents' experiences of school travel and their choices regarding travel mode with a focus on identifying barriers and facilitators to AST. Twenty parents of primary school children (4–12 years) in the West Yorkshire region took part in semi-structured interviews regarding school travel, informed by the Theoretical Domains Framework. Framework Analysis was used to identify key themes in the data and to develop a comprehensive picture of parents' experiences of school travel at both individual and structural levels. Distance was the biggest barrier to AST. Time constraints were reported as the main barrier to parents accompanying children in AST, while concerns about safety deterred parents from allowing children to travel independently. The need to incorporate multiple jouneys, such as the work commute and/or multiple school drop-offs, placed demands on parents' time, while difficulty getting children into local schools meant further to travel for a number of parents. Findings suggest that interventions to promote AST may be particularly effective if tailored towards working parents. However, also addressing factors such as distance to school and school travel at a policy level may produce more significant shifts in behaviour. Highlights: Distance was the biggest barrier parents reported to active school travel. Working parents were more likely to drive children to school. Perceived risk from traffic stops parents from letting children travel independently. Having to make multiple journeys made car use more likely.